Bulbophyllum abangjoei sp. Nov. (Orchidaceae: Dendrobieae), a new species of orchid from Sarawak - Go, Rusea; Besi, Edward Entalai; Hong, Kenny Eng Khor; Pungga, Runi Sylvester (MDPI, 2022)
Bulbophyllum abangjoei is a new one-flowered orchid species described from Lanjak Entimau Wildlife Sanctuary, Katibas and Anap-Muput, Tatau, Sarawak. The taxonomic treatment is accompanied by taxonomic notes, information on the species’ affinities at infrageneric level, geographical distribution, habitat ecology, and implications for their conservation. It is morphologically almost similar to Bulbophyllum deviantiae, B. membranifolium, and B. sanguineolentum, but clearly differs in the long, narrowly oblong to linear leaf blade, subsessile petiole ca. 5 mm long, long narrowly cylindrical pseudobulbs with some mature pseudobulbs reaching ¾ length of the leaf blade, non-resupinate flowers, shortly upcurved and not emarginate labellum apex, and elliptic-oblong stelids at lower margins near the apex of the column. For these morphological differences, B. abangjoei is here described as distinct and new species to science. The new species is so far only known from three localities in protected areas in Sarawak, and hereby is assessed as ‘Endangered’ [EN B2 (a)(b) D1] under IUCN Red List criteria B and D.